2023
DOI: 10.3390/children10020290
|View full text |Cite
|
Sign up to set email alerts
|

Lung Function in Children with Primary Ciliary Dyskinesia

Abstract: Background: Primary ciliary dyskinesia (PCD) is characterized by impaired mucociliary clearance that results in accumulation of mucus and bacteria in the airways. Lower respiratory tract infections lead to airway remodeling and lung function impairment. The aim of our narrative review is to discuss available data on lung function in PCD children, focusing on risk factors for lung function impairment. Methods: Relevant published studies searching MEDLINE/Pubmed are included in this narrative review, using these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…In PCD, lung abnormalities such as mucus plugging, peri‐bronchial thickening and bronchiectasis lead to impaired lung functions, increased work of breathing and decreased QOL 30 . In the study mentioned earlier, mean FEV1 and forced vital capacity of the whole group were lower than normal; when stratified by age, children aged 6−9 years had the smallest impairment 5 .…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In PCD, lung abnormalities such as mucus plugging, peri‐bronchial thickening and bronchiectasis lead to impaired lung functions, increased work of breathing and decreased QOL 30 . In the study mentioned earlier, mean FEV1 and forced vital capacity of the whole group were lower than normal; when stratified by age, children aged 6−9 years had the smallest impairment 5 .…”
Section: Discussionmentioning
confidence: 84%
“…FEF 25−75 was in the lower limit of normal and LCI was increased, consistent with small airway obstruction. Previous studies found that LCI is more sensitive than FEV1 to detect early lung disease, and may correlate with CT findings 30,31 . In a study comparing PCD, CF and healthy controls, FEV1 was similarly reduced in PCD and CF, while FEF 25−75 and maximal expiratory pressure were lower in PCD 7 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Lung function testing is considered a parameter for evaluating the severity of exacerbation in these patients [ 8 ]. It is important to recognize the risk factors and to monitor the follow-up in terms of exacerbation and lung function in these patients, as well as in the subgroup of children with primary ciliary dyskinesia [ 9 , 10 ]. As already evidenced in cystic fibrosis, Pseudomonas aeruginosa represents the most relevant risk factor for both exacerbation and lung function worsening [ 11 ].…”
mentioning
confidence: 99%